Methodology for Determining the Compliance Matrix and Analyzing the Skew Anisotropic Plate with an Arbitrarily Shaped Hole - Xiaoli Zhang; Aizhong Lu; Kezhi Song; Guangming Wu; Lei Wang (Advances in Materials Science and Engineering)
The previous analytical methods mainly focused on the analysis of orthotropic, transversely isotropic, or even isotropic materials, and little analyses have been conducted on nonorthogonal and extreme anisotropic material properties. In this study, the infinite skew anisotropic plate with an arbitrary-shaped hole are considered. Initially, two local Cartesian coordinate systems are established along the skew orientations in the plate, and the equations for the elastic constants of the material are established according to the transformation formulae under rotation of the coordinate axes. On this basis, the elastic compliance matrix for the skew anisotropic material can be obtained in combination with the engineering constants (Young’s modulus, Poisson’s ratio, and shear modulus). Subsequently, the complex variable method is utilized to derive the analytical solutions for stress along the hole boundary. The elliptical, hexagonal, and square holes perforated in skew anisotropic plates are used as examples, respectively, and the stress distributions along the hole boundary are analyzed for different external loadings. Finally, the theoretical method presented in this paper is verified by means of the Finite Element Analysis of ANSYS software.